2011
DOI: 10.1037/a0021995
|View full text |Cite
|
Sign up to set email alerts
|

Teaching with concrete and abstract visual representations: Effects on students' problem solving, problem representations, and learning perceptions.

Abstract: In 3 experiments, we examined the effects of using concrete and/or abstract visual problem representations during instruction on students' problem-solving practice, near transfer, problem representations, and learning perceptions. In Experiments 1 and 2, novice students learned about electrical circuit analysis with an instructional program that included worked-out and practice problems represented with abstract (Group A), concrete (Group C), or abstract and concrete diagrams (Group AC), whereby the cover stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 82 publications
4
67
0
3
Order By: Relevance
“…Moreno et al [4] study involving electrical engineering students as subjects revealed some interesting observations regarding concrete and abstract representations. Participants received instructions using abstract representations (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreno et al [4] study involving electrical engineering students as subjects revealed some interesting observations regarding concrete and abstract representations. Participants received instructions using abstract representations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…light bulbs) and both concrete and abstract representations. Moreno et al [4] stated that in the past research studies, concrete representations had been shown to distract from learning compared to abstract representations. However, Moren, Ozogul and Reisslein's new study showed that the greatest learning occurred when a combination of concrete and abstract representations was used.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling is an essential capability for MIS graduates whether as part of a programming task, for modeling a business problem or process, and for modelling additional tasks required within the development process of an information system. The use of decision trees is also an opportunity to show and discuss with the students the power of diagramatic representations for modeling (Bredeweg & Forbus, 2003), for decision making (Lurie & Mason, 2007), and for problem solving (Larkin & Simon, 1987;Moreno, Ozogul, & Reisslein, 2011). In our course we tried to use or add diagrammatic representations, on top of the required use of decision trees, whenever it was appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…This study explores the use of multiple student-generated and computer-generated representations as a feasible mechanism to improve conceptual understanding of electric circuits [8][9][10] . Thus, the guiding research questions are: How effectively do students use multiple representations of electric circuits?…”
Section: Background and Motivationmentioning
confidence: 99%
“…A main concern for educational researchers and educators has been finding ways to improve current learning techniques to consequently improve students' conceptual understanding. Examples of such strategies consist of including computational and laboratory activities, and components of cyberlearning tools used along with traditional materials.This study explores the use of multiple student-generated and computer-generated representations as a feasible mechanism to improve conceptual understanding of electric circuits [8][9][10] . Thus, the guiding research questions are: How effectively do students use multiple representations of electric circuits?…”
mentioning
confidence: 99%